Mitochondrial encephalocardio-myopathy with early neonatal onset due to TMEM70 mutation. Issue 4 (24th March 2010) - Honzík, Tomáš; Tesařová, Markéta; Mayr, Johannes A; Hansíková, Hana; Ješina, Pavel; Bodamer, Olaf; Koch, Johannes; Magner, Martin; Freisinger, Peter; Huemer, Martina; Kostková, Olga; van Coster, Rudy; et al.
Abstract : Objective: Mitochondrial disturbances of energygenerating systems in childhood are a heterogeneous group of disorders. The aim of this multi-site survey was to characterise the natural course of a novel mitochondrial disease with ATP synthase deficiency and mutation in the TMEM70 gene. Methods: Retrospective clinical data and metabolic profiles were collected and evaluated in 25 patients (14 boys, 11 girls) from seven European countries with a c.317-2A→G mutation in the TMEM70 gene. Results: Severe muscular hypotonia (in 92% of newborns), apnoic spells (92%), hypertrophic cardiomyopathy (HCMP; 76%) and profound lactic acidosis (lactate 5–36 mmol/l; 92%) with hyperammonaemia (100–520 µmol/l; 86%) were present from birth. Ten patients died within the first 6 weeks of life. Most patients surviving the neonatal period had persisting muscular hypotonia and developed psychomotor delay. HCMP was non-progressive and even disappeared in some children. Hypospadia was present in 54% of the boys and cryptorchidism in 67%. Increased excretion of lactate and 3-methylglutaconic acid (3-MGC) was observed in all patients. In four surviving patients, life-threatening hyperammonaemia occurred during childhood, triggered by acute gastroenteritis and prolonged fasting. Conclusions: ATP synthase deficiency with mutation in TMEM70 should be considered in the diagnosis and management of critically ill neonates with early neonatal onset of muscular hypotonia, HCMP and hypospadias in boys accompanied by lactic acidosis, hyperammonaemia and 3-MGC-uria. However, phenotype severity may vary significantly. The disease occurs frequently in the Roma population and molecular-genetic analysis of the TMEM70 gene is sufficient for diagnosis without need of muscle biopsy in affected children.